Donations and tax incentives: Evidence from South Africa - Fadzayi Chingwere; Matthew Clance; Nicky Nicholls; Aimable Nsabimana; Eleni Yitbarek (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This study examines the impact of tax incentives on charitable donations within South Africa, with a focus on donations declared on individuals' tax returns. Leveraging the universe of South African tax administrative data spanning over a decade (2011-21), we apply the bunching approach to assess how individual taxpayers respond to donation tax incentives. South Africa's tax policy allows individuals to deduct up to 10% of their taxable income for contributions made to approved public benefit organizations, with the option to carry forward any excess donations for potential deductions in future years. Our findings indicate significant bunching at the cap, demonstrating a considerable tax price elasticity of giving at the intensive margin, which suggests a high responsiveness of charitable donors to tax incentives. Variation in bunching patterns has been observed across different demographics, such as gender, age, and income percentiles. We also estimate the heterogeneous implied tax price elasticity of donations. The findings show that the implied tax price elasticity of donations was higher for females than for males. The study also finds that working-age individuals and the less wealthy showed higher responsiveness to the tax incentive. Although only a small proportion of taxpayers report donations and we are not able to determine whether additional donations are made but not reported, our results suggest that tax deduction incentives could increase charitable donations.
Keywords: H21; H24; H32; 330; charity donations; tax incentive policy; South Africa